NOTION OF DEATH IN AMERICAN AND UZBEK LITERATURE (Konferensiyalar | Conferences, 2024)
This article delves into the portrayal of death in American and Uzbek literature, exploring the cultural, historical, and philosophical perspectives that shape each society's interpretation of mortality. Through an examination of prominentliterary works and authors from both traditions,the article highlights the diverse ways in which death is conceptualized and depicted, ranging from existential contemplation to spiritualreflection. By comparing and contrasting these representations,the article seeks to illuminate the universalthemes and cultural nuances surrounding the human experience of death in two distinctliterary traditions